The discursive ethos from enunciation to the construction of self-image - ZAIMECHE , Khadidja (Journal of Human Sciences, 2023)
From ethos to discursive ethos, a passage from rhetoric to the analysis of discourse, common foundations but different processes, identifying the ethos said and shown, the types of ethos based on criteria enunciative and various linguistics, such is the object of our study. This multidisciplinary study is limited to the analysis of the relationship that can link discursive ethos and prediscursive ethos, it takes as its starting point the enunciative and linguistic aspect of the discourse to identify the ethos of the speaker and the image that he gives of himself.